(untitled) (Al-Academy, 2019)
It is not new to say that recent studies have tended to look at the margins of the texts in order to extract the information provided by the book to the recipient. The margins of the texts were defined in a number of terms, including the thresholds, and the margins of the text, etc. The difference was according to the researchers who dealt with the subject in research and inquiry. Therefore, all researchers assert that the texts must provide information even if it is propaganda for the text. Hence the importance of these texts emerged as they represent a scientific information material that encapsulates the body of the text as well as being a propaganda material that inspires the reader to read it. Hence for the importance of the subject, this research is made of five main sections. The first dealt with the research problem, which was: what is the iconicity of the textual thresholds and their role in highlighting the meaning in the crime scenario? The aim of the present study is to reveal the implications of the textual thresholds as icons surrounding the scenario of the crime film. The second section includes the theoretical framework and has been divided into two sections: First, what is the textual threshold, and second: the sections and types of text thresholds. The third: the research procedures. The research methodology was the analytical descriptive method, and the sample was the scenario of the film "The Departed". The fourth section was an analysis of the sample of the research and finally the fifth section presented the results and conclusions and the most important was: The textual thresholds, psychologically and mentally prepare the reader to enter into the midst of a scenario conflict. The coded image of the cover, which brought together the three characters of the film and the recipient knew that such a picture never existed in the film, had a role in suggesting the interconnectedness through the hidden relationships between them, though the two characters (Billy) (Colin) had met at the end of the film yet the character (Costello) is the only one who dealt with the two characters since the beginning of the scenario. So the cover image illustrates these relationships well.